2020
DOI: 10.3892/etm.2020.9524
|View full text |Cite
|
Sign up to set email alerts
|

SARS‑CoV‑2, multiple sclerosis, and focal deficit in a postpartum woman: A case report

Abstract: SARS-CoV-2 infections raise many practical concerns in a woman with multiple sclerosis (MS) during the perinatal period. On the other hand, the impact of COVID-19 on patients with MS and disease-modifying therapies (DMTs) is unknown. We report on a female patient who was treated with interferon beta 1a (IFNB-1a) for many years for relapsing-remitting multiple sclerosis (RRMS) until December 2018. She developed COVID 19 infection in April 2020, after giving birth to a healthy baby girl, five weeks before. She d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Fifteen case reports and case series reported the occurrence of MS relapse/pseudo-relapse or the onset of a first demyelinating event consistent with MS or CIS in 19 patients ( 57 , 63 , 65 69 , 76 79 , 81 , 82 , 84 , 86 ). Twelve observational case series and cohort studies documented the occurrence of relapses or pseudo-relapses among patients with a known diagnosis of MS and confirmed diagnosis of COVID-19 ( 58 61 , 64 , 71 75 , 83 , 85 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen case reports and case series reported the occurrence of MS relapse/pseudo-relapse or the onset of a first demyelinating event consistent with MS or CIS in 19 patients ( 57 , 63 , 65 69 , 76 79 , 81 , 82 , 84 , 86 ). Twelve observational case series and cohort studies documented the occurrence of relapses or pseudo-relapses among patients with a known diagnosis of MS and confirmed diagnosis of COVID-19 ( 58 61 , 64 , 71 75 , 83 , 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most MS/CIS cases received treatment with IVMP 1 gram for 3–5 days ( 57 , 61 , 65 , 68 , 76 , 77 , 79 , 80 , 82 ) and had a favorable outcome ( 57 , 65 , 68 , 77 82 ). Treatment of pseudo-relapses was primarily focused on COVID-19 management, with return to baseline neurological status upon infection recovery ( 63 , 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…She was discharged after two consecutive negative PCRs. After two weeks, PCR, IgG, and IgM for SARS-CoV-2 were negative, along with the remission of the neurological deficit [127].…”
Section: Does Infection Of Sars-cov-2 May Be An Actual Neurodegeneratmentioning
confidence: 98%
“…Women with MS in the postpartum period are even more vulnerable to relapses and infections. Another case report of SARS-CoV-2 infection in a 40-year-old woman with recurrent RRMS demonstrated that the relapse of MS began right after SARS-CoV-2 infection [127]. Five weeks postpartum, the patient complained of paresthesia and disability in the right limbs, with the onset two weeks before.…”
Section: Does Infection Of Sars-cov-2 May Be An Actual Neurodegeneratmentioning
confidence: 99%
“…This is particularly true regarding the neurologic manifestations associated with this type of viral infection. Neurological events linked to COVID-19 infection range from mild to severe, life-threatening complications [ 2 ]. Myalgia, headache, dizziness, encephalopathy, anosmia, and dysgeusia appear to be more common, while stroke, seizures, sensory deficits, motor deficits, ataxia, and movement disorders have also been reported, but with a lower prevalence [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%